Innovation in Urology Telerobotic Surgery in Improving Treatment Effectiveness and Safety through a Systematic Journal Review - Franiko, Rendy; Suhendra, Edward Julio; Thevany, Thevany (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Telerobotic surgery, a specialized field of telesurgery utilizing robotic instruments for remote procedures, has revolutionized surgical precision, reduced invasiveness, and minimized complications. The integration of 5G technology further enhances real-time communication, enabling seamless remote operations. This advancement is particularly beneficial in addressing healthcare disparities, allowing expert surgical interventions in remote and underserved regions. Urological procedures, including those for bladder, kidney, and prostate cancers, have notably benefited from these innovations. However, significant challenges remain, including high costs, complex training requirements, and cybersecurity concerns, which hinder widespread adoption. This study aims to systematically review innovations in urological telerobotic surgery, highlighting its key benefits in improving treatment efficacy and patient safety. A systematic journal review was conducted using a descriptive qualitative approach with thematic synthesis to assess recent innovations and their impact on patient outcomes. Findings indicate that cutting-edge robotic systems such as the da Vinci Single Port (SP) and Senhance improve precision while reducing patient trauma. Artificial intelligence (AI) supports postoperative planning, while 5G technology facilitates real-time remote surgeries. Studies suggest that robotic-assisted procedures yield shorter operation times, reduced complications, and quicker recovery compared to traditional laparoscopy. Despite its benefits, the high costs, infrastructure demands, and extensive training requirements present barriers to widespread implementation. Addressing these challenges requires collaboration between healthcare providers and the technology sector to enhance accessibility and affordability. As advancements continue, telerobotic surgery holds the potential to redefine surgical care, improving patient outcomes and expanding healthcare access globally.